2019
DOI: 10.1177/1352458519863764
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of multiple sclerosis risk among Hispanic and African American populations living in the United States

Abstract: Background: Substantial progress has been made toward unraveling the genetic architecture of multiple sclerosis (MS) within populations of European ancestry, but few genetic studies have focused on Hispanic and African American populations within the United States. Objective: We sought to test the relevance of common European MS risk variants outside of the major histocompatibility complex ( n = 200) within these populations. Methods: Genotype data were available on 2652 Hispanics (1298 with MS, 1354 controls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Consistent with previous reports, 2,17 the Hispanic subjects in our cohort were more likely to present with optic neuritis and transverse myelitis at onset, to have a higher risk for development of ambulatory disability, and to lose employment as a result of disease compared to Caucasians with MS. Epidemiological data in MS suggest that socioeconomic disparities and barriers to healthcare access may account, at least in part, for the differences in clinical outcome across racial groups. 18,19 However, due to the lack of significant socioeconomic disparities between our matched study cohorts, the racial/ethnic differences we identified cannot be ascribed to socioeconomic factors alone, and may be better explained by a complex interaction between genetic predisposition and environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports, 2,17 the Hispanic subjects in our cohort were more likely to present with optic neuritis and transverse myelitis at onset, to have a higher risk for development of ambulatory disability, and to lose employment as a result of disease compared to Caucasians with MS. Epidemiological data in MS suggest that socioeconomic disparities and barriers to healthcare access may account, at least in part, for the differences in clinical outcome across racial groups. 18,19 However, due to the lack of significant socioeconomic disparities between our matched study cohorts, the racial/ethnic differences we identified cannot be ascribed to socioeconomic factors alone, and may be better explained by a complex interaction between genetic predisposition and environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous replication study in Hispanics and African Americans [8], we found that not all of the 200 currently identified variants were replicated among these minority populations. In fact, less replication was found than expected, particularly among African Americans.…”
Section: Introductionmentioning
confidence: 74%
“…This inconsistency could be due to limited participant engagement, making it difficult to attain the sample sizes necessary to achieve adequate power. This is true in Hispanic and African American MS study samples (with sizes currently approaching ~2000 cases and ~2000 controls in the Alliance for Research in Hispanic MS (ARHMS)) [8]; while European MS study samples currently approach 110,00 in the IMSGC (~50,000 MS cases and ~60,000 controls) [1]. Yet, the admixture and unique LD structure of Hispanics and African Americans make them distinctly valuable for localizing association signals and identifying causal variants, despite the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations